Alcohol, cannabis, and tobacco polysubstance use: A latent profile analysis of age of onset. Issue 1 (1st December 2022) - Stamates, Amy L.; Roberts, Rhiannon; Lau-Barraco, Cathy
Abstract: Background: Despite understanding the long-term risks associated with early substance use, less is known about the specific patterns of the age of onset (AO) across multiple substances and whether these patterns of early exposure are linked to substance use later in young adulthood. Consequently, the present study sought to (1) identify distinct classes regarding AO for alcohol, cannabis, and tobacco and (2) compare these classes on patterns of individual and simultaneous alcohol, cannabis, and tobacco use, other substance use, and mental health symptoms. Methods: Participants were 510 emerging adults ( M age = 21.35; 88.6% men) who reported past-year use of alcohol, cannabis, and tobacco. Results: Latent profile analysis was used to identify classes based on three indicators: AO for alcohol, cannabis, and tobacco. Results revealed that four classes best fit the data: Earliest AO for Alcohol (19.8%); Latest AO for Substances (6.5%); Late AO for Substances (67.8%); Earliest AO for Cannabis and Tobacco (5.9%). Classes varied on current patterns of individual substance use, co-use of substances, other illicit drug use, and mental health symptomology. The Latest AO of Substances class reported the lowest alcohol use, cannabis use, other illicit drug use, and mental health symptomology than the other classes. The Earliest AO for Alcohol and the Late AO of Substances reported a lower frequency of tobacco compared to the other classes. The Late AO of Substance class reported the highest past-year frequency of simultaneous alcohol and cannabis use. Conclusions: The current study contributed to the larger polysubstance literature by identifying profiles that may signify risky patterns of use. Findings may help guide prevention and intervention work with adolescents and young adults.